DEVELOPMENT OF INSTRUCTIONAL MATERIALS WRITING POETRY BASED ON NATURE TOURISM FOR POETRY LEARNING - Galang Prasetyo Aji; Yuni Pratiwi; Nita Widiarti (Jurusan Sastra Indonesia, 2018)
Teaching materials is one of the government's alternatives in its efforts to achieve educational goals. Interesting learning process is a learning that uses resources, media, and various other learning support, especially textbooks. Once the importance of the book as a learning resource, it is important for us to develop it, especially the material to write poetry. A teaching material to write poetry will be more interesting for students if the theme is focused and more deeply when writing poetry, so the selection of natural tourism theme is determined so that students more easily in writing and understanding poetry. Creation of a teaching material is intended to make it easier for students to understand about nature-based poetry. This article will discuss the essence of teaching materials, the characteristics of teaching materials, the essence of poetry, the purpose of writing poetry, and learning about writing natural-based poetry as an effort to help understand the poetry of nature.